Construction Actors' Perception and Readiness for Environmentally Friendly Soil Improvement in Green Infrastructure Practices - Soehardi, Fitridawati; Rahmat, Hendri; Idris, Marlaily (Journal of Infrastructure and Civil Engineering, 2025)
This study aims to assess the perceptions and readiness of construction practitioners regarding the implementation of environmentally friendly soil improvement methods in green infrastructure practices. The study used a descriptive quantitative approach, using a 20-item questionnaire involving 51 respondents active in construction projects. The validity and reliability of the instrument were tested using Pearson correlation and Cronbach's Alpha coefficients, with the majority of items being declared valid (r-value> 0.278) and very high reliability (? = 0.940). The descriptive analysis showed that respondents' understanding of the basic principles of environmentally friendly soil improvement methods was high (mean = 4.08), reflecting a growing awareness of sustainability concepts in geotechnical engineering. However, respondents also identified several implementation barriers, both technical, such as limited equipment and a lack of operational standards, and non-technical, such as budget constraints, resistance to innovation, and minimal local stakeholder participation. Policy support was also deemed insufficiently concrete to encourage the widespread adoption of these methods. The correlation analysis demonstrated a positive relationship between understanding and awareness of implementation challenges. These findings underscore the importance of a collaborative approach and stronger regulatory support to accelerate the adoption of green technologies in the construction sector. The study recommends strengthening technical training, enhancing the capacity of project actors, and developing sustainability-based incentive policies.